Pengembangan Penilaian Autentik Keterampilan Berbahasa Tulis Di Sekolah Dasar - Rosayu, Witgia Indah; Mustoip, Sofyan (EduBase : Journal of Basic Education, 2020)
This study aims to (1) find out the profile of writing assessment in elementary schools today. (2) explain the prototype of developing authentic assessment of written language skills in elementary schools. (3) describes the results of the implementation of the prototype development of an authentic assessment instrument for written language skills in elementary schools. This research was conducted using research and development methods that refer to the Sukmadinata steps, namely preliminary studies, development stages and trials. Products for developing written language authentic assessment instruments consist of (1) assessment instruments for writing book reports; (2) instrument for writing rhymes assessment; (3) poetry writing evaluation instruments and; (4) attitude assessment instruments in writing activities. The results of this development research are (1) authentic assessment instruments writing book reports, rhyming writing, poetry writing and attitude assessment in writing activities declared valid by assessment experts and practitioners; (2) the consistency of kappa coefficient> 0.775 in the consistency test of the book writing assessment instrument means that the rhyme writing assessment instrument obtains the average kappa coefficient value> 0.709, and the poetry writing evaluation instrument obtains an average value of kappa coefficient> 0.651 which means that the instrument Valuation of writing book notes, rhymes and poetry has a high consistency in the assessment by several assessors. Thus the authentic assessment developed was declared valid and reliable so that it could be used as an alternative to written language assessment instruments in elementary schools. Abstrak Penelitian ini bertujuan untuk (1) mengetahui profil penilaian menulis di Sekolah Dasar saat ini. (2) memaparkan prototipe pengembangkan penilaian autentik keterampilan berbahasa tulis di Sekolah Dasar. (3) memaparkan hasil implementasi prototipe pengembangan instrumen penilaian autentik keterampilan berbahasa tulis di Sekolah Dasar. Penelitian ini dilaksanakan dengan menggunakan metode penelitian dan pengembangan yang mengacu pada langkah-langkah Sukmadinata yaitu studi pendahuluan, tahap pengembangan dan uji coba. Produk pengembangan instrumen penilaian autentik berbahasa tulis terdiri dari (1) instrumen penilaian menulis laporan buku; (2) instrumen penilaian menulis pantun; (3) instrumen penilaian menulis syair dan; (4) instrumen penilaian sikap dalam kegiatan menulis. Hasil penelitian pengembangan ini yaitu (1) instrumen penilaian autentik menulis laporan buku, menulis pantun, menulis syair dan penilaian sikap dalam kegiatan menulis dinyatakan valid oleh ahli penilaian dan praktisi; (2) dalam uji kekonsistenan instrumen penilaian menulis buku diperoleh nilai rata-rata koefisien kappa > 0,775, instrumen penilaian menulis pantun memperoleh nilai rata-rata koefisien kappa > 0,709, dan instrumen penilaian menulis syair memperoleh nilai rata-rata koefisien kappa > 0,651 artinya instrumen penilaian menulis catatan buku, pantun dan syair memiliki kekonsistenan yang tinggi dalam penilaian oleh beberapa penilai. Dengan demikian penilaian autentik yang dikembangkan dinyatakan valid dan reliabel sehingga dapat digunakan sebagai alternatif instrumen penilaian berbahasa tulis di Sekolah Dasar